ANALISIS MANAJEMEN RISIKO OPERASIONAL PADA USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) ‘’MIE AYAM JAMUR RESTU’’ MEDAN SELAYANG - Nur Astiah Rahma; Anna Tie Etika Sesti Mendrofa; Ade Tri Hartanti; Aulia Nazwa; Ayunda Fatmasari (Journal of Innovative and Creativity (Joecy), 2026)
Objective – The objective of this study is to analyze the operational risks faced by the MSME "Mie Ayam Jamur Restu" and to formulate risk mitigation strategies dan SOP that can be implemented to support the business's sustainability. Novelty – This study offers insights into risk management implementation within an MSME setting by utilizing risk identification, risk assessment, and the formulation of mitigation strategies based on actual field conditions. Method – This study employs a qualitative descriptive method. Data collection was conducted through observation and direct interviews at the "Mie Ayam Jamur Restu" MSME, located at Jalan Sei Belutu No. 58, Padang Bulan Selayang I, Medan Selayang District, Medan City. Findings – The findings indicate the presence of several operational risks at "Mie Ayam Jamur Restu," namely power outages, fire hazards, QRIS payment disruptions, service errors, equipment or gas stove malfunctions, raw material delivery delays, and raw material spoilage. The risks with the highest severity levels were equipment or gas stove malfunctions (score: 12), raw material spoilage (score: 9), and service errors (score: 6). Limitations and Implications – This study was conducted on a single MSME ("Mie Ayam Jamur Restu") and did not compare risk management practices with similar businesses. However, the results can serve as a reference for business owners in managing operational risks to enhance service quality and ensure business sustainability.